The Relationship between College Students’ Perceptions of Colleague Education, Major Satisfaction and Employability (Medico Legal Update, 2019)
Background/Objectives: This study aimed to investigate the relationship between college students’ perceptions of colleague education, major satisfaction and employability.Method/Statistical analysis: The survey was conducted from December1 to 20, 2017 in the subjects of the students who were informed of the study goals and contents, and agreed. First for the sociodemographic characteristics, they were set including sex, religion, entrance type, type of admission, a native high school, living environment, family economic status, study level perceived by him or her. And we surveyed the data ofperceptions of colleague education, major satisfaction and employability.Findings: Upon the study results among 121freshman, they showed mean values of perceptions of colleague education, major satisfaction and employability with 50.73 ± 5.82 points, 35.87 ± 5.34 points and 85.10 ± 12.38 points, respectively. When looking at correlations to look at relationships between perceptions of colleague education, major satisfaction, and satisfaction employability, there is a significant amount of correlation between the three variables.Improvements/Applications: It is intended to help develop interventions that can look at the current state of students and increase their degree satisfaction and employment potential.